Students’ Objective Needs in Learning to Write: An Overview on the EFL Teaching and Learning Practice - Banu, Tri Buce J.; Benu, Sonya V. Ch.; Wulandari, Heidy (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
Writing in English has been so long becoming a required skill for EFL learners to master. However, to being well-qualified in this skill is not easy, since students should undergo systematic processes by learning and internalizing every single aspect of the language and the usage. Thus, students certainly have needs to be considered by English teachers when teaching. Definitely, every student has different  personal competence that requires intensive guidance. This study is aimed at finding out and describing the Basic Writing students of STKIP SoE English Education Program objective needs in learning to write in English. Descriptive qualitative was applied as the method and 24 students who just finished with their Basic Writing class were the participants. Students’ writing drafts, reflective statements and interview were used to collect the data. Based on the data from the instruments, the result showed that almost all of the students were weak in applying the language aspects including grammar, vocabulay mechanism, consistency of sentence and ideas construction, paragraph structure and coherence in writing. Here, the problems convey valuable information for EFL teachers on how to consider better teaching implementation to improve the students’ competence in English particularly in writing skill to create well-qualified writers in the future. Beside that, enligthening the teachers on what to consider in teaching writing from the basic to the higher writing levels.